2021
DOI: 10.1093/ajcn/nqaa299
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed food consumption is associated with increased risk of all-cause and cardiovascular mortality in the Moli-sani Study

Abstract: Background Consumption of ultra-processed food (UPF) is gaining growing attention in relation to disease/mortality risk, but less is known on the main nutritional factors or biological mechanisms potentially underlying such associations. Objectives We aimed to assess the association between UPF and mortality risk in a large sample of the Italian adult population and test which nutritional factors were on the pathway of this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
143
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 34 publications
7
143
1
3
Order By: Relevance
“…Growing evidence has accumulated that the consumption of ultra-processed foods has positive associations with metabolic health [7,13,[53][54][55][56][57][58][59] such as obesity, hypertension, dyslipidemia, and diabetes, cardiovascular diseases [12,14], cancer [60,61], and mortality [9,62,63]. The adverse impacts of ultra-processed foods on human health have been explained by the poor nutrient profile of these foods [3,17], the low dietary quality [3,4,11,33] associated with the consumption of these foods, and the addictive eating behaviors induced by these foods, which may lead to overconsumption [7,64].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has accumulated that the consumption of ultra-processed foods has positive associations with metabolic health [7,13,[53][54][55][56][57][58][59] such as obesity, hypertension, dyslipidemia, and diabetes, cardiovascular diseases [12,14], cancer [60,61], and mortality [9,62,63]. The adverse impacts of ultra-processed foods on human health have been explained by the poor nutrient profile of these foods [3,17], the low dietary quality [3,4,11,33] associated with the consumption of these foods, and the addictive eating behaviors induced by these foods, which may lead to overconsumption [7,64].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the relevant contribution of UPF to daily energy intake, it has been evaluated whether UPF intake is associated with adverse health outcomes. Interestingly, observational studies have suggested that the consumption of UPF is associated with a higher risk of cardiovascular diseases, metabolic diseases, cancer, and all-cause and cardiovascular mortality [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We calculated iF P ro for 20,047 individuals with dietary records in a representative U.S. national sample from NHANES 1999-2006. As Figure 3C shows, the median iF P ro W C for the American population is 0.7872, confirming a high reliance on intake on ultra-processed food [24][25][26]. More importantly, iF P ro allows us to identify differential reliance on processed food.…”
Section: Individual Processing Scorementioning
confidence: 74%
“…• Ultra-processed food consumption is associated with increased risk of all-cause and cardiovascular mortality in the Moli-sani Study [26] Molise, Italy (Moli-sani)…”
Section: Environment-wide Association Studymentioning
confidence: 99%